2019
DOI: 10.1002/jez.2310
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography and electrocardiography reveal differences in cardiac hemodynamics, electrical characteristics, and thermal sensitivity between northern pike, rainbow trout, and white sturgeon

Abstract: Doppler and B‐mode ultrasonography and electrocardiography (ECG) were used to determine cardiac hemodynamics and electrical characteristics in 12°C‐acclimated and metomidate‐anesthetized northern pike, rainbow trout and white sturgeon (7–9 per species) at 12°C and 20°C, and at a comparable heart rate (fH, ~60 beats/min). Despite similar relative ventricle masses and cardiac output (Q), interspecific differences were observed at 12°C in fH, ventricular filling and ejection, stroke volume, the duration ECG inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…It is reported that the heart and ventilation rates decreased in Atlantic sturgeon (A. oxyrhynchus) at 100 mg/L MS-222 concentration (Matsche, 2011). Similarly results have been reported in rainbow trout and white sturgeon (A. transmontanus) following anesthesia by metomidate (Ma et al, 2019). Present study showed that the heart rate decreased in Danube sturgeon exposed to 80 μl/L clove oil treatment.…”
Section: -Pesupporting
confidence: 86%
See 1 more Smart Citation
“…It is reported that the heart and ventilation rates decreased in Atlantic sturgeon (A. oxyrhynchus) at 100 mg/L MS-222 concentration (Matsche, 2011). Similarly results have been reported in rainbow trout and white sturgeon (A. transmontanus) following anesthesia by metomidate (Ma et al, 2019). Present study showed that the heart rate decreased in Danube sturgeon exposed to 80 μl/L clove oil treatment.…”
Section: -Pesupporting
confidence: 86%
“…Echocardiographic measurements of fish in anesthesia studies might enable a more accurate assessment of the anesthetic efficacy (Aydın & Orhan, 2021). However, few studies on the cardiographic monitoring of fish under anaesthesia are available in the literature (Aydın & Barbas, 2020; Aydın & Orhan, 2021; Ma et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The HR of G. rufa induced with 50 μl/L eugenol was similar to the normal HR of C. carpio of the same family Cyprinidae (Dziaman et al, 2010). It was also similar to the normal HR of northern pike Esox lucius (61.5 ± 1.4 beats/min) and matrinxã Brycon amazonicus (65.0 ± 3.7 beats/min) (Ma et al., 2019; Monteiro et al., 2017). As in this study, MS‐222 + isoflurane did not cause reduction of HRs in D. rerio (Huang et al., 2010).…”
Section: Discussionsupporting
confidence: 72%
“…Brycon amazonicus (65.0 ± 3.7 beats/min) (Ma et al, 2019;Monteiro et al, 2017). As in this study, MS-222 + isoflurane did not cause reduction of HRs in D. rerio (Huang et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation